Willingness to pay entrance fees to natural attractions : an Icelandic case study - Reynisdottir, M; Song, H; Agrusa, J (Tourism Management, 2014)
2008-2009 > Academic research: refereed > Publication in refereed journal Accepted Manuscript Published